House by house, block by block : the rebirth of America's urban neighborhoods - Von Hoffman, Alexander (OUP E-Books., 2003)
Not long ago, neighborhoods such as the South Bronx, South Central Los Angeles, and Boston's Roxbury were crime-ridden wastelands of vacant lots and burned-out buildings, notorious symbols of urban decay. In House by House, Block by Block, Alexander von Hoffman tells the remarkable stories of how local activists and community groups helped turn these areas around.